Desenvolvimento e estudo de óxidos de manganês lítio e carbonatos fosfatos obtidos por métodos solvotérmicos assistidos por micro-ondas para aplicação em baterias recarregáveis - Demétrio Abreu Sena Costa (2019)
This work was based on the development of a fast and an ultra-fast synthetic methods with high rate kinetics where some cathodic materials of the lithium manganese oxide class, LixMnyOz, and of the sodium carbonate phosphate class, Na3MCO3PO4, as Sidorenkite like structures, Na3MnCO3PO4, had their synthesis applied and optimized in the solvothermal microwave assisted method. They were characterized and studied as insertion cathodic materials in aqueous media. Through this microwave assisted solvothermal method the unpublished R-3m lithium rich Li[Li0,145Mn0,855]O2 disposed as a lamellar phase was synthesized. At the very first time was announced the achievement of a lamellar lithium rich phase where there is only manganese as the transition metal. This fact can be considered an effort to fulfill the lack of new applicable lithium compounds in the energy storage market. This method has produced some materials with an interesting range of morphologies, two of them are unpublished for the Na3MCO3PO4 compounds yet, case of the hexagonal Na3CoCO3PO4 nano plates and the Na3NiCO3PO4 star fruit like micro particles. As well as for the LixMnyOz compounds that have showed very tiny particles with grains smaller than 10 nm. The Li[Li0,145Mn0,855]O2 has been able to reach a discharge capacity of 160 mA.h/g. While the Na3MnCO3PO4 synthesized for only 5 processing minutes has showed an electrochemical performance similar to the as one made with 30 processing minutes. Both of one retains discharges capacities around 60 mA.h/g after third complete charge/discharge cycles.